Strengthening Nutrition Interventions through Academic Collaboration in Pasaman Barat, Indonesia - Gusnedi Gusnedi; Nur Ahmad Habibi; Renidayati Renidayati; Irmawartini Irmawartini; Heppi Sasmita; Delima Delima; Mardiani Bebasari; Renita Afriza; Dwi Octa Amalia; Hamdani Hamdani; Citra Tristi Utami (Media Publikasi Cendekia Indonesia, 2026)
This study aims to strengthen evidence-based policymaking for stunting reduction in Pasaman Barat District, Indonesia, through a collaborative model linking academic institutions and with local government. A situation analysis was conducted to assess program coverage, implementation challenges, and multisectoral support related to stunting prevention. Quantitative data from 20 primary health centers showed that most specific nutrition intervention indicators below the national minimum target of 80%. A pilot strengthening program was then implemented, focusing on improving cadre capacity, service supervision, community engagement, and data management. Post-intervention results demonstrated statistically significant improvements in growth monitoring (54.49%±27.19 to 97.43%±5.26; p = 0.00), exclusive breastfeeding (19.04%±28.47 to 59.28%±37.38; p = 0.00), and iron–folic acid supplementation among pregnant women (22.28%±16.96 to 85.28%±24.62; p = 0.00). Other indicators, including complementary feeding practices, antenatal care visits, and adolescent anemia screening, showed numerical but non-significant changes. Qualitative findings further revealed challenges related to limited cadre skills, inadequate facilities, insufficient intersectoral coordination, low community participation, and inconsistent data quality. The developed collaboration model facilitated closer integration of research evidence into local decision-making and supported the formulation of strategic policy recommendations. Overall, the study highlights that institutionalized academic–government partnerships, combined with continuous monitoring and strengthened health system capacity, are essential to accelerate meaningful and sustained reductions in stunting in Pasaman Barat.